A case report of fatal anaphylaxis on first exposure to rasburicase just before lymphoma treatment - Yoshikazu Utsu; Natsuho Kaneda; Makio Kawakami; Shin-ichi Masuda; Hironori Arai; Sonoko Shimoji; Rena Matsumoto; Takafumi Tsushima; Kazusuke Tanaka; Kosuke Matsuo; Chiharu Kimeda; Shiho Konno; et al. (Allergy, Asthma & Clinical Immunology)
Abstract Background Rasburicase, a recombinant urate oxidase enzyme, has potent efficacy in controlling uric acid and is widely used to prevent tumor lysis syndrome in high-risk patients owing to its low toxicity profile. However, it has been associated with a risk of anaphylaxis, especially on re-exposure, owing to its immunogenic potential. Case presentation A 71-year-old Japanese female diagnosed with diffuse large B cell lymphoma with a large tumor burden experienced anaphylactic shock leading to death upon initial administration of rasburicase. The pre-and postmortem examination revealed that the cause of death was a cascade of events starting with anaphylaxis-induced distributive shock leading to obstructive shock due to the collapse of the heart, which was compressed by the post-mediastinal tumor. This was further compounded by massive bleeding from the tumor and tension hemothorax, resulting in circulatory collapse. Conclusions Although extremely rare, rasburicase can cause fatal anaphylaxis, even on first exposure.